A study of weed populations and their buried seeds in the soil of MARDI research station and at farmers' rice fields in Sungai Burung, Tanjung Karang, Selangor, Malaysia - B. S., Ismail; Koay, Phaik Hong (Universiti Putra Malaysia Press, 2004)
A study of weed populations and their buried seeds before and after harvesting was carried out at the MARDI Research Station and at Farmers' Rice Fields, Sungai Burung in Tanjung Karang, Selangor. The results showed that the broadleaf weeds were the most dominant in the MARDI and Sungai Burung rice fields. Two species, namely Cyperus difformis (sedge) and Najas graminae (broadleaj) were the most dominant species in the MARDI and Sungai Burung rice fields respectively. The weed seed populations were similar in both rice fields. However, the weed seed counts before and after harvesting were different. In general, it was also found that the highest number of weed seeds in the soil was detected in the 0-5 cm layer of soil in both rice fields.